2012
DOI: 10.1177/1076029612440034
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulability in End-Stage Liver Disease: Prevalence and Its Correlation With Severity of Liver Disease and Portal Vein Thrombosis

Abstract: Contrary to well-recognized bleeding diathesis in chronic liver disease, thrombotic events can occur in these patients due to reduction or loss of synthesis of anticoagulant proteins. Forty-seven consecutive patients with end-stage liver disease (ESLD) were investigated for activity of protein C, protein S, antithrombin, and factor V Leiden mutation. Forty-two (89.4%) patients had low levels of at least 1 while 33 (70.2%) patients were deficient for all anticoagulant proteins studied. Forty-six (97.9%) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…The other natural anticoagulants analysed did not show this trend. This finding further validates the role of PrC in plasmatic hypercoagulability in CLD as theorized in previous studies Tripodi et al observed decreased plasma PrC levels in cirrhosis (median of nearly 40%) in patients with CLD and they showed that a PrC‐deficient status contributed to the high index of procoagulant imbalance in these patients. Our results of significant decrease in PrC levels with increasing severity of liver dysfunction support this concept that there occurs a state of procoagulant imbalance in CLD due to reduced PrC.…”
Section: Discussionsupporting
confidence: 89%
“…The other natural anticoagulants analysed did not show this trend. This finding further validates the role of PrC in plasmatic hypercoagulability in CLD as theorized in previous studies Tripodi et al observed decreased plasma PrC levels in cirrhosis (median of nearly 40%) in patients with CLD and they showed that a PrC‐deficient status contributed to the high index of procoagulant imbalance in these patients. Our results of significant decrease in PrC levels with increasing severity of liver dysfunction support this concept that there occurs a state of procoagulant imbalance in CLD due to reduced PrC.…”
Section: Discussionsupporting
confidence: 89%
“…In liver disease, the endogenous anticoagulants as well as procoagulant factors are all reduced, and the balance of procoagulants to anticoagulants may be altered in favor of a prothrombotic state, but the INR reflects primarily procoagulant activity . It is increasingly recognized that patients with cirrhosis are at risk of thrombotic complications as a result of low endogenous anticoagulant levels . Viscoelastic monitoring adds valuable qualitative information to the management of these cases …”
Section: Discussionmentioning
confidence: 99%
“…40 It is increasingly recognized that patients with cirrhosis are at risk of thrombotic complications as a result of low endogenous anticoagulant levels. 41 Viscoelastic monitoring adds valuable qualitative information to the management of these cases. 42 What remains unclear is what action should be taken when hypercoagulability is demonstrated on TEG.…”
Section: Discussionmentioning
confidence: 99%
“…33 While coagulation function is altered by liver dysfunction, anticoagulant factors such as protein S decrease in a higher proportion in patients with cirrhosis. 6 Thus, a relatively hypercoagulable state can develop with a large amount of protein S consumed after the formation of PVT. Both liver function deterioration and PVT formation can contribute to decreased protein S concentrations, which have been associated with venous thromboembolism and ischaemic stroke.…”
Section: Discussionmentioning
confidence: 99%